A phenomenological description of BslA assemblies across multiple length scales - Morris, Ryan J. (Philos Trans A Math Phys Eng Sci, 2016)
Intrinsically interfacially active proteins have garnered considerable interest recently owing to their potential use in a range of materials applications. Notably, the fungal hydrophobins are known to form robust and well-organized surface layers with high mechanical strength. Recently, it was shown that the bacterial biofilm protein BslA also forms highly elastic surface layers at interfaces. Here we describe several self-assembled structures formed by BslA, both at interfaces and in bulk solution, over a range of length scales spanning from nanometres to millimetres. First, we observe transiently stable and highly elongated air bubbles formed in agitated BslA samples. We study their behaviour in a range of solution conditions and hypothesize that their dissipation is a consequence of the slow adsorption kinetics of BslA to an air–water interface. Second, we describe elongated tubules formed by BslA interfacial films when shear stresses are applied in both a Langmuir trough and a rheometer. These structures bear a striking resemblance, although much larger in scale, to the elongated air bubbles formed during agitation. Taken together, this knowledge will better inform the conditions and applications of how BslA can be used in the stabilization of multi-phase materials. This article is part of the themed issue ‘Soft interfacial materials: from fundamentals to formulation’.